The Rise of AI in the Creative Industry: Threat or Opportunity for Human Artistry? (KALAA SAMIKSHA, 2025)
Artificial intelligence (AI) has entered the creative industries in ways once thought impossible, producing artwork, literature, and music that closely mimic human creation. Long considered resistant to automation, creativity has been defined by its personal, experiential, and emotional dimensions qualities that machines cannot replicate. Yet, the popularity of AI-generated art, from stylised portraits to algorithmic poetry, raises urgent questions about the future of human artistry. This article examines the paradox AI presents: on one hand, it showcases remarkable technological progress and novel tools for creative practice; on the other, it risks devaluing human labour, authenticity, and cultural meaning. By drawing attention to the commodification of art and the precarious conditions of many creators, it argues that what is at stake is not simply employment, but the very soul of artistic expression. The challenge is to embrace innovation without surrendering what makes creativity irreducibly human.